Undocumented migrants lack access to pregnancy care and prevention - Andreoli Nicole; Delieutraz-Marchand Jacqueline; Costanza Michael C; Lourenco Ana P; Epiney Manuella; Wolff Hans; Dubuisson Jean-Bernard; Gaspoz Jean-Michel; Irion Olivier (BMC, 2008)
Abstract Background Illegal migration is an increasing problem worldwide and the so-called undocumented migrants encounter major problems in access to prevention and health care. The objective of the study was to compare the use of preventive measures and pregnancy care of undocumented pregnant migrants with those of women from the general population of Geneva, Switzerland. Methods Prospective cohort study including pregnant undocumented migrants presenting to the University hospital from February 2005 to October 2006. The control group consisted of a systematic sample of pregnant women with legal residency permit wishing to deliver at the same public hospital during the same time period. Results 161 undocumented and 233 control women were included in the study. Mean ages were 29.4 y (SD 5.8) and 31.1 y (SD 4.8) (p < 0.02), respectively. 61% of undocumented women (controls 9%) were unaware of emergency contraception (OR 15.7 (8.8;28.2) and 75% of their pregnancies were unintended (controls 21%; OR 8.0 (4.7;13.5)). Undocumented women consulted for an initial pregnancy visit more than 4 weeks later than controls and only 63% had their first visit during the first trimester (controls 96%, p < 0.001); 18% had never or more than 3 years ago a cervical smear test (controls 2%, OR 5.7 (2.0;16.5)). Lifetime exposure to violence was similar in both groups, but undocumented migrants were more exposed during their pregnancy (11% vs 1%, OR 8.6 (2.4;30.6)). Complications during pregnancy, delivery and post-partum were similar in both groups. Conclusion Compared to women who are legal residents of Geneva, undocumented migrants have more unintended pregnancies and delayed prenatal care, use fewer preventive measures and are exposed to more violence during pregnancy. Not having a legal residency permit therefore suggests a particular vulnerability for pregnant women. This study underscores the need for better access to prenatal care and routine screening for violence exposure during pregnancy for undocumented migrants. Furthermore, health care systems should provide language- and culturally-appropriate education on contraception, family planning and cervical cancer screening.